Transcription Factor Deformed Wings Is an Atg8a-Interacting Protein That Regulates Autophagy - Marta Kołodziej; Panagiotis Tsapras; Alexander D. Cameron; Ioannis P. Nezis (Cells)
LC3 (microtubule-associated protein 1 light chain 3, called Atg8 in yeast and Drosophila) is one of the most well-studied autophagy-related proteins. LC3 controls the selectivity of autophagic degradation by interacting with LIR (LC3-interacting region) motifs also known as AIM (Atg8-interacting motifs) on selective autophagy receptors that carry cargo for degradation. Although the function of Atg8 family proteins is primarily cytoplasmic, they are also enriched in the nucleus. Despite the accumulating evidence indicating the presence of Atg8 proteins in the nucleus, the mechanisms by which they are targeted to the nucleus, their interactions with nuclear components, and their nuclear role in remain poorly understood. Here, we used yeast two-hybrid screening, and we identified transcription factor Deformed wings (Dwg) as an Atg8a-interacting protein in Drosophila. Dwg-Atg8a interaction is LIR motif-dependent. We have created Dwg Y129A/I132A LIR mutant flies and shown that they exhibit elevated autophagy, improved resistance to oxidative stress, and starvation. Our results provide novel insights into the transcriptional regulation of autophagy in Drosophila.